Insights into the function of ESCRT complex and LBPA in ASFV infection - Barrado-Gil, Lucía; García-Dorival, Isabel; Galindo, Inmaculada; Alonso, Covadonga; Cuesta-Geijo, Miguel Ángel (Frontiers in Cellular and Infection Microbiology, 2023)
ASFV is strongly dependent on an intact endocytic pathway and a certain cellular membrane remodeling for infection, possibly regulated by the endosomal sorting complexes required for transport (ESCRT). The ESCRT machinery is mainly involved in the coordination of membrane dynamics, hence, several viruses exploit this complex and its accessory proteins VPS4 and ALIX for their own benefit. In this work, we found that shRNA-mediated knockdown of VPS4A decreased ASFV replication and viral titers and this silencing resulted in an enhanced expression of ESCRT-0 component HRS. ASFV infection slightly increased HRS expression but not under VPS4A depletion conditions. Interestingly, VPS4A silencing did not have an impact in ALIX expression, which was significantly overexpressed upon ASFV infection. Further analysis revealed ALIX silencing impaired ASFV infection at late stages of the viral cycle, including replication and viral production. In addition to ESCRT, the accessory protein ALIX is involved in endosomal membrane dynamics in a lysobisphosphatydic acid (LBPA) and Ca2+ dependent manner, which is relevant for intraluminal vesicles (ILV) biogenesis and endosomal homeostasis. Also, LBPA interacts with NPC2 and/or ALIX to regulate cellular cholesterol traffic, and would affect ASFV infection. Thus, we show that LBPA blocking impacted ASFV infection both at early and late infection, suggesting a function for this unconventional phospholipid in ASFV viral cycle. Here, we found for first time that silencing of VPS4A and ALIX affect later on the infection and blocking LBPA function reduces ASFV infectivity at early and later stages of the viral cycle, while ALIX was overexpressed upon infection. These data suggested the relevance of ESCRT related proteins in ASFV infection.